Komparasi Surface Rehabilitation dan Deep Rehabilitation pada Revitalisasi Stasiun Ponorogo - Agustin, Camelia Putri; Mufidah, Mufidah; Santoso, Joko (Universitas muhammadiyah palembang, 2023)
Ponorogo Station is a non-active station located in Ponorogo Regency, East Java, Indonesia. In the Ponorogo Regency Regional Regulation No. 1 of 2012 concerning the 2012-2032 Ponorogo Regency Regional Spatial Plan, the Ponorogo Regency Government is trying to revitalize Ponorogo Station. In revitalizing it is necessary to have an approach chosen to be implemented. Therefore, a comparison of the surface rehabilitation and deep rehabilitation approaches was carried out at the Ponorogo Station by looking at the issues and problems in the existing conditions. Since it was no longer active, Ponorogo Station has experienced a decrease in vitality, changes in function and damage due to 'self' and 'new creations' which make Ponorogo Station no longer intense. So, the right steps to respond to problems and optimize revitalization at the Ponorogo Station can be with a deep rehabilitation approach.